Financial markets, banking and the design of monetary policy: A stable baseline scenario - Florian Hartmann; Peter Flaschel (Economies, 2014)
A baseline integration of commercial banks into the disequilibrium framework with behavioral traders of Charpe et al. (2011, 2012) is presented. At the core of the analysis is the impact the banking sector exerts on the interaction of real and financial markets. Potentially destabilizing feedback channels in the presence of imperfect macroeconomic portfolio adjustment and heterogeneous expectations are investigated. Given the possible financial market instability, various policy instruments have to be applied in order to guarantee viable dynamics in the highly interconnected macroeconomy. Among those are open market operations reacting to the state-of-confidence in the economy and Tobin-type capital gain taxes. The need for policy intervention is even more striking, as the banking sector is modeled in a rather stability enhancing way, fulfilling its fundamental tasks of term transformation of savings and credit granting without engaging in investment activities itself.
Keywords: 330; monetary business cycles; portfolio choice; credit and banking; (in-)stability; stabilizing policy measures